A novel function of lipid droplets in regulating longevity. (21st September 2009) - Goldberg, Alexander A.; Bourque, Simon D.; Kyryakov, Pavlo; Boukh-Viner, Tatiana; Gregg, Christopher; Beach, Adam; Burstein, Michelle T.; Machkalyan, Gayane; Richard, Vincent; Rampersad, Sonia; Titorenko, Vladimir I.
Abstract : Growing evidence supports the view that LDs (lipid droplets) are dynamic organelles that can serve both as an intracellular signalling compartment and as an organizing platform orchestrating many vital processes in eukaryotic cells. It has become clear that the LDs-confined deposition and lipolytic degradation of neutral lipids define longevity in multicellular eukaryotic organisms and yeast. We summarize the evidence in support of the essential role that LDs play in longevity regulation and propose several molecular mechanisms by which these dynamic organellar compartments control the aging process in multicellular eukaryotes and yeast.